Seeds - Turner, M. (Technical Centre for Agricultural and Rural Cooperation, 2011)
Seeds are a key element in most farming systems and play a vital role in the development of agriculture and the growth of civilisations. Providing a clear understanding of seed production and supply – with particular reference to tropical conditions – this title covers topics such as: plant breeding, seed harvesting and processing, marketing and enterprise management. Whether you’re a farmer or are interested in becoming a seed supplier, this practical field guide holds a wealth of knowledge and information.